1976
DOI: 10.1152/ajplegacy.1976.230.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of lung fluids in acute alloxan edema in dogs

Abstract: In 11 anesthetized dogs with acute alloxan-induced pulmonary edema, we measured the protein composition of 1-mul samples of plasma, free interstitial fluid, alveolar fluid, and airway fluid. We obtained plasma and airway fluid at regular intervals as edema developed. We sampled alveolar fluid by pleural micropuncture in the unfrozen, excised lung and free interstitial fluid from perivascular cuffs in the frozen, excised lung. The average (+/- 1 SD) total protein concentration of plasma was 4.9 +/- 0.6, airway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Vreim et al (3) showed that in high pressure pulmonary edema, with the extravascular lung water-to-dry weight ratio ranging from 6.6 to 15.7, the alveolar flooding was less obvious. However, they had much less difficulty producing alveolar flooding in low pressure pulmonary edema (2). A recent study by Julien et al (19) shows that the amount of lung water present in low pressure pulmonary edema may have been underestimated by expressing it per gram of bloodfree dry tissue.…”
Section: Fitc Tracer Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vreim et al (3) showed that in high pressure pulmonary edema, with the extravascular lung water-to-dry weight ratio ranging from 6.6 to 15.7, the alveolar flooding was less obvious. However, they had much less difficulty producing alveolar flooding in low pressure pulmonary edema (2). A recent study by Julien et al (19) shows that the amount of lung water present in low pressure pulmonary edema may have been underestimated by expressing it per gram of bloodfree dry tissue.…”
Section: Fitc Tracer Studiesmentioning
confidence: 99%
“…In a subsequent study Vreim and Staub (2) also showed that in alloxaninduced low pressure pulmonary edema (LPPE),1 alveolar flooding occurs more readily and the fluid has a higher protein content and an increased number of cells compared with high pressure pulmonary edema (HPPE) (3). These observations suggest that epithelial permeability may be quite different under the two conditions, and this is supported by the observations that HPPE clears rapidly with therapy (4) compared with LPPE, which takes days to resolve (5).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies in which alveolar fluid was obtained by direct alveolar micropuncture have shown that the protein concentration of alveolar fluid is similar to that of fluid in the airways in both cardiac and permeability types of pulmonary edema [19,20]. Clinical studies have shown that the analysis of edema protein relative to plasma protein concentrations is useful in separating these two types of pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…In typical "cardiogenic" pulmonary edema, recruitment of capillary bed results in an increased surface area available for macromolecular flux, whereas an increase in convective forces leads to greater flux per unit surface area (2)(3)(4). In "noncardiogenic" pulmonary edema, a "capillary-leak syndrome," with impairment of the normal molecular sieving function of the endothelial membrane, results in veritable "flooding" of the interstitium with oncotically active proteins (5)(6)(7). Clinical measurement of transvascular protein flux in lung may aid in early diagnosis of pulmonary edema, and allow differentiation between "cardiogenic" and "noneardiogenic" types based on the magnitude of detected changes.…”
Section: Introductionmentioning
confidence: 99%